Basic and other measurements of radiation at station Syowa (1994-01 et seq) - Hisamitsu, Junji; Ijima, Osamu; Ogawa, Yutaka; Tanaka, Yoshinobu; Ogihara, Hiroyuki; Fukuda, Masato; Kawashima, Koji; Doi, Motohisa; Yamanouchi, Takashi (National Institute of Polar Research, Tokyo, 2023)
This is a compilation of all short-wave and long-wave radiation datasets from Syowa that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).